(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Discourse analysis creatively combines for the first time viewpoints from linguistics, language use, cognitive linguistics, and language acquisition. It has been complicated to see how investigation from each of these fields may challenge, inform, and enrich the others because of the long distance between nations and regions, as well as the barriers between various theories and subfields within linguistics. In addition to encouraging more collaborative research, the article tries to make these constraints more clear.